2011
DOI: 10.1093/annonc/mdq321
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after radical hysterectomy according to tumor size divided by 2-cm interval in patients with early cervical cancer

Abstract: tumor size divided by a 2-cm interval was an independent prognostic factor and correlated well with other risk factors and with the need for adjuvant therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
34
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 33 publications
6
34
0
Order By: Relevance
“…We found that 29.3% of patients with tumors >4 cm in diameter were cured by RH alone without RT, consistent with the rates of 37-51% previously observed in patients with bulky early-stage cervical cancer [6,7,16,17]. Many more patients than expected did well after surgery alone, and such patients experienced the best survival outcomes and the lowest morbidity rates, indicating that RH continues to play a significant role in patients with bulky early-stage cervical cancer.…”
Section: Discussionsupporting
confidence: 89%
“…We found that 29.3% of patients with tumors >4 cm in diameter were cured by RH alone without RT, consistent with the rates of 37-51% previously observed in patients with bulky early-stage cervical cancer [6,7,16,17]. Many more patients than expected did well after surgery alone, and such patients experienced the best survival outcomes and the lowest morbidity rates, indicating that RH continues to play a significant role in patients with bulky early-stage cervical cancer.…”
Section: Discussionsupporting
confidence: 89%
“…However, this should be balanced against the increased local failure rate of primary radiotherapy reported in patients with large tumors 20,21 and the advantages of surgery, such as accurate staging, resection of bulky positive nodes, and ovarian preservation. Radical hysterectomy is feasible in large tumors; in a study by Park et al, 16 there were no significant differences with regard to either the complication rate or incidence of positive margins, among patients with tumor sizes greater than 2 cm. Therefore, both treatment options (primary radiotherapy and RH) should be offered to the patients, with discussion including clear communication regarding the high likelihood of receiving adjuvant radiation if surgery is chosen, with the associated risks.…”
Section: Discussionmentioning
confidence: 89%
“…Similar results have been reported by others as well. 16,17 In a study by Park et al, 16 the probability of having intermediate risk factors (eg, lymphovascular space invasion, deep stromal invasion) and high risk factors (eg, parametrial involvement and lymph node metastasis) increased with increase in tumor size from 2 cm or lesser to greater than 6 cm. Considering the increased morbidity associated with combined treatment, 18,19 the risk of adjuvant radiation should be taken into account when contemplating RH in these patients.…”
Section: Discussionmentioning
confidence: 98%
“…It is generally acknowledged that LVSI, tumor size ≥ 4 cm, and deep cervical stromal invasion are intermediate-risk factors [2]- [4]. Pelvic lymph node metastasis, positive resection margin, and parametrial invasion are all considered as high-risk factors.…”
Section: Discussionmentioning
confidence: 99%